Konstytucyjna zasada poszanowania praw człowieka w procesie integracji europejskiej - od wspólnoty do zbieżności aksjologicznej - Bainczyk, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the process of constitutionalization of the European Union human rights protection has become one of the most prominent values. It constitutes both a condition for the membership in the EU but also a value which shall be observed by European institutions and Member States in accordance with Article 7 of the Treaty on the European Union. Nevertheless, the principle of protection of human rights derived form national constitutional law seems to have evolved into one of the most popular obstacles to the process of European integration, applied by national constitutional courts. The Polish Constitutional Court has adopted the same posi-tion. Ten years ago the Polish Court spoke about the “axiological community”; however, it has recently changed its attitude, initiated a constitutional control of secondary EU law and used the term of “axiological convergence” instead of community. Besides, the constitutional prin-ciple of human rights protection has also been defined by the Polish Constitutional Court as an element of the principle of constitutional identity, which shall be preserved in the process of European integration. The crucial point is how the above-mentioned axiological conver-gence will be interpreted by the Polish Court.
Keywords: Trybunał Konstytucyjny; prawa człowieka; prawo UE; integracja europejska; tożsamość konstytucyjna